Política de formação profissional do SENAI e a qualidade de vida no trabalho: o olhar dos egressos - SOARES FILHO, José do Egypto Vieira (Universidade Federal do Pará, 2011)
This study it presents a research where if the politics of professional formation of the SENAI-PA argues, from the depositions of egresses of courses in the area of industrial learning, of the institution, whose theoretical aiming is based on the Quality of Life of the Work. Theoretically, we consider the influence of the Theory of the Capital Human and the pointers of QVT, destacadamente the economic one, the politician, psychological and the sociological one in the formation of industrial apprenticees. The central question was to answer as the professional formation gotten by the egresses of the SENAI reflected in its quality of life in the work. It enters the specific objectives of general order and, are distinguished, to develop a study on the situation of the egresses of the courses of the SENAI of the Center of Professional Formation "Getúlio Vargas" in Belém-Pará, the period of 2000 the 2003; to identify the egresses of the Course of Industrial Learning; to verify the insertion in the professional field of these egresses; to analyze the professional and partner-economic expectations of the egresses on the basis of the QVT pointers and to contribute for the deepening of the processes of institucional evaluation of the Center of Professional Formation, in intention to syntonize the strategical performance of the SENAI with the yearnings and necessities of the community. The depositions objects of our study had been gotten in interviews with former-pupils, in which you say disclose them the importance given for them to the professionalism, to the attainment of income to leave of this profession and of the necessary professional perfectionings, in face to the incited dispute in the market of work force, in the partner-economic conjuncture globalizada contemporary. For moreover, this work also makes possible a historical reflection on the evolution of the SENAI, detached integrant of the System "S" and firing pin of politics of professional education in Brazil, deriving of the delayed initial phase of Brazilian industrialization. In the analysis, we still look for to more disclose basic aspects that must be pursued by the public politics - in special relative to the professional education with all the beings executors of this politics, wants private public or -, in terms of adequacy of its lines of direction in favor of a professional formation for the needed people than it takes care of the necessity of a standard of Quality of Life, equivalent to the world-wide parameters.